The Iconography of Chicano Self-Determination: Race, Ethnicity, and Class - Goldman, Shifra M. (Art Journal, 1990)
In several cities in the Southwest and Midwest with sizable enclaves of Chicanos, there are to be found considerable numbers of images that have become leitmotifs of Chicano art. In their ubiquity, these motifs demonstrate that the Chicano phase of Mexican-American art (from 1965 to the 1980s) was nationally dispersed, shared certain common philosophies, and established a network that promoted a hitherto nonexistent cohesion. In other words, it was a movement, not just an individual assembly of Mexican-descent artists. In what follows, Chicano art is examined as statements of a conquered and oppressed people countering oppression and determining their own destiny, though not all the producers of these images necessarily saw their production in the political way they are framed below. Examples have been chosen specifically to show how, in response to exploitation, artists have taken an affirmative stance celebrating race, ethnicity, and class.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Kent Monkman : entre ré/appropriation et « Painting Back ». - Pancaldi, Valentina (Artelogie. Recherche sur les arts, le patrimoine et la littérature de l'Amérique latine, 2018)
À la suite d’une série d’évènements historiques de grande relevance sociopolitique, les années 1990 ont connu une montée d'initiatives menées par les artistes autochtones nord-américains visant à une récupération et une divulgation de leur l’héritage culturel, et, de ce fait, à une revendication de leur visibilité dans le panorama international. De cette résurgence, l’artiste multimédial autochtone canadien, Kent Monkman, constitue l’une des voix plus actives et plus emblématiques. En créant un dialogue épistémologique entre les études postcoloniales et l’art autochtone, cet article interrogera l’œuvre de Kent Monkman au prisme d’une notion dont sera proposée une définition, à savoir le « Painting Back ».
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; _Nettoyé

Imágenes de lo extraordinario. Memorias de un continente poblado por monstruos. - Gil, Slenka Leandra Botello; Camacho, Daianna Sierra (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
Este trabajo presenta los resultados de la investigación Imágenes de lo extraordinario: monstruos americanos del siglo XVI, proceso de creación artística desarrollado por los estudiantes del Semillero de Investigación en Artes Visuales (SINAV) del programa de Artes Visuales de la Universidad Nacional Abierta y a Distancia (UNAD) entre 2018 y 2019. Para analizar de manera crítica e histórica la construcción de identidades sobre lo latinoamericano, se tomó como marco de análisis la representación de lo monstruoso en los relatos y las imágenes construidas por los cronistas de Indias en el siglo XVI, los cuales marcaron procesos de marginalización cultural, construcción de subjetividades y dinámicas de poder, y presentaron al habitante americano como una otredad que estaba fuera de los límites de la cultura dominante occidental. Se presentan los postulados teóricos sobre lo monstruoso como marco para el análisis histórico y la creación de obra, con una metodología de trabajo colaborativo y en gran parte virtual. Posteriormente, se exponen algunos resultados de la investigación histórica que dan paso a detallar el proceso de creación de obra que culminó con la exposición de la instalación audiovisual Imágenes de lo extraordinario, así como con una amplia serie de ilustraciones contemporáneas sobre lo monstruoso y un producto digital en formato página web donde se presenta una cartografía de lo monstruoso en América Latina y se recogen las memorias de todo el proyecto. This work presents the results of the research Images of the Extraordinary: American Monsters of the 16th Century, artistic creation process developed by the students of the Research Seedbed in Visual Arts (SINAV, for its initials in Spanish) of the Visual Arts program of Universidad Nacional Abierta y a Distancia (UNAD) between 2018 and 2019. With the objective of analyzing, in a critical and historical way, the construction of identities on Latin American matters, the representation of the monstrous in the stories and images constructed by the chroniclers of the Indies in the 16th century was used as a framework of analysis. These chroniclers marked processes of cultural marginalization, construction of subjectivities and power dynamics, and presented the American inhabitant as an otherness that was outside the limits of the dominant Western culture. The theoretical postulates about the monstrous are presented as a framework for historical analysis and the creation of works, with a collaborative and largely virtual working methodology. Some results of the historical research are then presented, which gives way to detailing the process of creating work that culminated in the exhibition of the audiovisual installation Images of the Extraordinary, as well as a wide range of contemporary illustrations on the monstrous and a digital product in web page format where a cartography of the monstrous in Latin America is presented and the memories of the whole project are collected.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Interview with author, Dr. Laura Pérez - Ramirez, Abraham
Interview with author, Dr. Laura Pérez, Professor of Ethnic Studies at UC Berkeley on her most recent book, Eros Ideologies: Writings on Art, Sprituality, & the Decolonial.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Eros ideologies. Writings on art, spirituality, and the decolonial. - Perez, Laura E (Duke University Press, 2019)
In 'Eros Ideologies' Laura E. Perez explores the decolonial through Western and non-Western thought concerning personal and social well-being. Drawing upon Jungian, people-of-color, and spiritual psychology alongside non-Western spiritual philosophies of the interdependence of all life-forms, she writes of the decolonial as an ongoing project rooted in love as an ideology to frame respectful coexistence of social and cultural diversity. In readings of art that includes self-portraits by Frida Kahlo, Ana Mendieta, and Yreina D. Cervantez, the drawings and paintings of Chilean American artist Liliana Wilson, and Favianna Rodriguez's screen-printed images, Perez identifies art as one of the most valuable laboratories for creating, imagining, and experiencing new forms of decolonial thought. Such art expresses what Perez calls eros ideologies: understandings of social and natural reality that foreground the centrality of respect and care of self and others as the basis for a more democratic and responsible present and future. Employing a range of writing styles and voices-from the poetic to the scholarly-Perez shows how art can point to more just and loving ways of being.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Only Skin Deep: Changing Visions of the American Self - Fusco, Coco; Wallis, Brian (Abrams and International Center of Photography, 2003)
"By bringing together a provocative selection of essays and images, Only Skin Deep: Changing Visions of the American Self addresses the issues of nation, race, and selfhood and how they are depicted in ways that are challenging and informative, prompting readers to consider the impact of photography on our everyday lives." "If photographs are chiefly responsible for perpetuating myths of American identity, can a different reading of these representations break down distorting stereotypes? This is the central question posed by Only Skin Deep. The authors in this book forcefully argue that race and nation - and, indeed, photography itself - are fictions, cultural constructions that shape our social interactions. Even as symbols, these photographic depictions of ethnic difference and cultural superiority have very real consequences. This collection of works and essays addresses, for example, the lingering consequences of American colonial expansion; the conflict between public and private visualizations of individuals; the role of commercial imagery in shaping gender roles; the impact of fantasy in ethnic or ethnographic photography; and the uses of science to provide justification for politicized depictions of "race."" "Accompanying a major exhibition of the same name, Only Skin Deep offers a critical rereading of the archive of the history of photography. This applies to the works of famous photographers - such as Dorothea Lange, Walker Evans, Ansel Adams, and Edward Steichen - as well as lesser-known historical figures, including Charles Eisenmann, Frances Benjamin Johnston, Will Soule, and Toyo Miyatake. A substantial part of the book is devoted to contemporary artists and photographers who have moved beyond the multicultural approach to representations of "race" and have made an investigation of the semiotics of cultural identity a prevalent theme over the past decade. Among the recent photographers included are: Nancy Burson, Nikki S. Lee, Glenn Ligon, Paul Pfeiffer, Hulleah Tsinhnahjinnie, Cindy Sherman, Lorna Simpson, and Andres Serrano."--(BOOK JACKET)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Black Looks: Race and Representation - hooks, bell (Routledge, 2015)
"In the critical essays collected in Black Looks, bell hooks interrogates old narratives and argues for alternative ways to look at blackness, black subjectivity, and whiteness. Her focus is on spectatorship--in particular, the way blackness and black people are experienced in literature, music, television, and especially film--and her aim is to create a radical intervention into the way we talk about race and representation. As she describes: 'The essays in Black Looks are meant to challenge and unsettle, to disrupt and subvert.' As students, scholars, activists, intellectuals, and any other readers who have engaged with the book since its original release in 1992 can attest, that's exactly what these pieces do"(Provided by publisher)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Control mapping: Peter Pitseolak and Zacharias Kunuk on reclaiming Inuit photographic images and imaging - Winfield, Norman David (Decolonization: Indigeneity, Education & Society, 2014)
Inuit have been participating in the development of photo-reproductive media since at least the 19th century, and indeed much earlier if we continue on Michelle Raheja’s suggestion that there is much more behind Nanook’s smile than Robert Flaherty would have us believe. This paper examines how photographer Peter Pitseolak (1902-1973) and filmmaker Zacharias Kunuk have employed photography and film in relation to Raheja’s notion of “visual sovereignty” as a process of infiltrating media of representational control, altering their principles to visualize Indigenous ownership of their images. For camera-based media, this pertains as much to conceptions of time, continuity and “presence,” as to the broader dynamics of creative retellings. This paper will attempt to address such media-ontological shifts – in Pitseolak’s altered position as photographer and the effect this had on his images and the “presence” of his subjects, and in Kunuk’s staging of oral histories and, through the nature of film as an experience of “cinematic time,” composing time in a way that speaks to Inuit worldviews and life patterns – as radical renegotiations of the mediating properties of photography and film. In that they displace the Western camera’s hegemonic framing and time-based structures, repositioning Inuit “presence” and relations to land within the fundamental conditions of photo-reproduction, this paper will address these works from a position of decolonial media aesthetics, considering the effects of their works as opening up not only for more holistic, community-grounded representation models, but for expanding these relations to land and time directly into the expanded sensory field of media technologies.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé